LOW DENSITY AND VISCOSITY OF USED LUBRICANT OIL CONVERSION OVER ALPO4 CATALYST TOWARDS FUEL OIL - Agus Dani; Nurlia Pramita Sari; Haris Puspito Buwono (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
The conversion of used lubricating oil towards fuel oil by catalytic conversion is a suitable way to recycle waste oil. Catalyst has a key role in used lubricating oil conversion. Therefore this research was to study the catalytic cracking of used lubricating oil, and thus its properties as an alternative for fuel oil over aluminum fosfate. The experiments were carried out in a batch microreactor at a temperature of 350-400 oC, atmospheric initial air pressure, 5% w/w catalyst concentration, and reaction time of 5 min over aluminum fosfate catalyst. Aluminum fosfate catalyst produced low-density liquid product, and low viscosity of used lubricant oil conversion at any temperature of 350 – 400 oC, compared with those over alumina. Moreover, product converted at 400 oC is easy to flare. The credible reason for the low density and viscosity of AlPO4 can be proposed by three potentials: this catalyst is an acid type, the acid type is Bronsted and Lewis and this catalyst has a resistance toward contaminant.